Implementation of the implementation of worship in the family as a form of Christian Religious Education (PAK) of the family - Deasy Manutilaa (Electronic Journal of Education, Social Economics and Technology, 2025)
In the current era of globalization, challenges are increasingly emerging from various aspects of life. To address these challenges, it is necessary to instil a foundation of faith that begins in every family. The practice of worship within the family is a form of Christian religious education. Family worship plays a vital role in the spiritual and moral development of family members. Regular worship activities, such as prayer, Bible reading, and discussions about Christian teachings, not only strengthen faith but also shape children's character. Through family worship, the values of Christ's teachings can be instilled, creating an environment that supports spiritual and emotional growth. Furthermore, worshiping together serves as a means to strengthen relationships among family members, enhance communication, and teach the importance of love and understanding. Thus, the implementation of worship in families becomes a solid foundation for Christian learning, which is hoped to shape a generation with strong faith and responsibility in daily life.